SISTEM INFORMASI PENGELOLAAN DATA TAGIHAN AIR PAMSIMAS BERBASIS DESKTOP PADA KECAMATAN PADANG LAWEH - Meisa, Risma; Meisa, Risma Fera Apriani; Revita, Elinda; Purnomo, Wulan Andang (UNIVERSITAS STEKOM, 2025)
Information systems are one of the solutions that can facilitate the process of data input and management, one of which is payment administration and data management. The Community-Based Drinking Water and Sanitation Provision (PAMSIMAS) located in Padang Laweh village, Padang Laweh sub-district, Dharmasraya district. Currently, the PAMSIMAS water bill payment system is still collected from house to house, and data management only uses simple recording and books as monthly reports. Based on these issues, this research aims to design a Desktop-Based Data Management Information System for PAMSIMAS water bills, which is expected to assist in the administrative process efficiently and reduce the potential for calculation errors. This system was designed using Unified Modeling Language (UML), the Java programming language, and a MySQL database. Black-box testing results showed that all system functions performed as expected.